Impelementasi Ta’zimul ‘Ilmi wa Ahlihi dan Implikasinya dalam Mengoptimalkan Akhlak Santri di Pondok Pesantren Hidayatul Muta’alimin Air Gegas Kabupaten Bangka Selatan (EDOIS: Journal of Islamic Education, 2024)
Ta'zim is one of the qualities that students must have. It is said that a student of knowledge will not receive blessings if he abandons the quality of piety. However, what is happening now is that many students do not show this attitude, even though Islamic boarding schools are taught about ways to glorify knowledge and science experts, one of which is the Hidayatul Muta'allimin Islamic Boarding School. This research aims to determine the implementation of ta'zimul ilmi wa Ahlihi and its implications for efforts to optimize the moral development of santri.The type of research used was descriptive with a qualitative approach carried out at the Hidayatul Muta'allimin Islamic Boarding School, Air Gegas District. The research subjects were Islamic boarding school caregivers, dormitory caregivers, and Islamic boarding school students at Hidayatul Muta'allimin Islamic Boarding School using interview, observation and documentation data collection techniques. Researchers use triangulation of sources and techniques to test the validity of the data.The results of the research show that the implementation of ta'zimul ilmi wa Ahlihi at the Hidayatul Muta'allimin Islamic Boarding School goes through several processes, namely planning which is carried out by requiring all students to have a book of ta'lim al-Muta'allim, arranging schedules, and determining study methods and media. book. The implementation stage is using the bandongan, advice, pilot and habituation methods. The media used are yellow books and blackboards. The supervision stage is carried out by directly observing the dormitory caretaker, supervision of fellow students, and through Islamic boarding school regulations. The evaluation is carried out with sorogan and deliberation of the boarding school administrators. The implication of ta'zimul ilmi wa Ahlihi for santri is to increase their insight into the attitude of glorifying knowledge and experts, santri ethics and politeness, and being able to position themselves as seekers of knowledge.